Influence of growth retardants on productivity and profitability of Bt cotton in semi-arid region of north-western plain of India - Navish Kumar Kamboj; Gaurav Verma; Shabnam (Annals of Agricultural Research, 2024)
A field investigation was carried out during the kharif season of 2021 and 2022 at the cotton research station, Chaudhary Charan Singh Haryana Agricultural University, Hisar, Haryana to evaluate the influence of the growth retardants on performance of Bt cotton. The experiment was laid out in randomized block design with three replications. The treatments comprised viz., T1 , control; T2 , water spray; T3 , Mepiquat chloride (MC) @300 ppm at 90 DAS; T4 , Mepiquat chloride @300 ppm at 90 and 100 DAS; T5 , Mepiquat chloride @450 ppm at 90 DAS; T6 , Mepiquat chloride @450 ppm at 90 and 100 DAS; T7 , Maleic hydrazide(MH) @250 ppm at 90 DAS; T8 , Maleic hydrazide@250 ppm at 90 and 100 DAS; T9 , Maleic hydrazide@ 375 ppm at 90 DAS; T10 , Maleic hydrazide@ 375 ppm at 90 and 100 DAS. The results revealed that significantly higher performance [leaf area index (3.56), sympods branch per plant (13.8), main stem internodes (25.87), dry matter accumu lation at harvest stage (299.01 g/plant), open boll per plant (67.9), five boll weight (4.14 g), seed cotton yield (3329 kg/ha) and lower plant height (151.6 cm) of Bt cotton were recorded under T6 (Mepiquat chloride 450 ppm at 90 and 100 DAS) which was followed by T4 , T10 T5 and T8 comparison with control treatment. Simi larly, maximum economic [gross return (111996 /ha), net return (78072 /ha) and benefit cost ratio (2.30) was also recorded with the application of Mepiquat chloride (MC) @ 450 ppm at 90 and 100 DAS in comparison to the control treatment. Thus, application of Mepiquat chloride (MC) @ 450 ppm at 90 and 100 DAS may be recommended to farmers for getting higher seed cotton yield and economics of Bt cotton western-plain of India.